A high quality of Education grows from seeds of contentment: factors - Kengatharan, N. (My University, 2019)
Albeit the concept of job satisfaction is well entrenched in business and management research studies, there is a vacuum and piecemeal approach into educational settings. The factors determining job satisfaction of teachers are inclined to country-culture specific nature, thereby responding to the acknowledgement of the need by unearthing teachers’ perception of job satisfaction from a neglected cultural perspective. Anchored in philosophical assumptions, this research adopted the interpretivist-inductive approach. Using a purposive sampling technique, a total of twenty-three informants were chosen from the teaching profession and the required data were garnered from semi-structured interviews. This study revealed the factors determining teachers’ job satisfaction, viz., economic conditions, relationship with principals and colleagues, students’ behaviour, loosen policy towards students’ discipline, responsibility of parents, salary, teaching facilities, working environment, teachers training, teacher transferring policy, school holidays, familiarity with teaching, promotion policy, educational policies and status in society and those subsumed into tripartite form: cultural factors, economic factors, and national factors. This study unequivocally contributed to the frontiers of teachers’ job satisfaction literature and flagged up several avenues for future research.
Keywords: Teachers’ Job satisfaction; Educational settings; Country-cultural specific factors